The effects of salary and fringe benefits to the job satisfaction of law librarians in Metro Manila - Capitin, Dorothy B.; Santos, Antonio M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1994)
This study sought to find out the effect of salaries and fringe benefits to the job satisfaction of law librarians in Metro Manila. Also, it discussed the prevailing salaries, fringe benefits, factors affecting the salaries and fringe benefits, and the job satisfaction level of the law librarians.
The main data gathering instrument used in this study is the questionnaire. Samples were drawn based on the concept of inferential data analysis while profile analysis and assessment of respondents' salaries and fringe benefits were used as major techniques for analyzing data. To test the relationship between salaries, fringe benefits and job satisfaction of law librarians, the Chi square test of independence was used.
The study included 58 law librarians from 21 law libraries in Metro Manila. The findings of the study showed that the mean of the basic gross annual salary of librarians is P 81,655.117, where thirty-six (63.07) fall below the mean and only twenty-two (37.93) are above the mean. In the gross annual professional income, forty (68.97) of the salaries fall below the mean, while only eighteen (31.03) are above P105,241.38. A total of 31 fringe benefits is enjoyed by the librarians in varying quantity and among the benefits which are often enjoyed are the: 13-month pay, Christmas bonus, clothing allowance/uniform, COLA, and medical benefit. On job satisfaction, law librarians, in general, proved to be fairly satisfied with their job since most respondents gave a 3 and above job satisfaction rating.
From the findings of the study, the following conclusions may be stated: the basic gross annual salary does not affect job satisfaction; the gross annual professional income, instead significantly affects job satisfaction; the salaries and fringe benefits of law librarians are influenced by the type of library and the number of degrees attained by the librarian while sex, age, and years of professional library experience do not influence salaries and benefits.
To improve the job satisfaction of law librarians the following recommendations are given: the minimum professional income should be pegged at Salary Grade 20 in order to cope with the poverty threshold; library associations should make sure that salaries and fringe benefits are commensurate to the educational attainment of librarians; librarians should pursue continuing education; librarians should voice out their sentiments for the profession; and law librarians should work for the conversion of the diploma in law librarianship into a full degree.
Thesis (M.L.S.)--University of the Philippines, Diliman
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Law librarians--Job satisfaction--Philippines--Manila Metropolitan Area; Law librarians--Salaries, pensions, etc.--Philippines--Manila Metropolitan Area